Growing Trade in Intermediate Goods: Outsourcing, Global Sourcing or Increasing Importance of MNE Networks? - Jörn Kleinert (Kiel Institute of World Economics (IfW), 2000)
Trade in intermediate goods as one possible link between rising trade and foreign direct investment is examined. To explain growing intermediate goods trade, three hypotheses are brought forward: outsourcing, global sourcing and the increasing importance of MNE networks. These hypotheses are tested by employing a cross-section framework, which uses OECD input-output table data, and an analysis, which relies on German time-series data. Increasing importance of MNE networks is found to be a reason of growing trade in intermediate goods in the cross-section and the time-series framework. The evidence for outsourcing and global sourcing is found to be much weaker.
Keywords: F23; F11; F21; 330; Globalization; Intermediate Goods Trade; Outsourcing; Global Sourcing; Multinational Enterprise; Vorprodukt; Außenhandel; Internationale Arbeitsteilung; Schätzung; Outsourcing; Direktinvestition; Beschaffung; international; Multinationales Unternehmen; Firmeninterner Handel; Input-Output; OECD-Staaten; Deutschland